Variations on a Theme By Koetter - Kem Hinton (Oz, 1988)
Guidelines For A New District The Miller Park Urban Design and Development Guidelines were prepared to establish the planning of a new environment around downtown Chattanooga's southern-most outdoor amenity, Miller Park...